PEMBELAJARAN AL-QUR’AN UNTUK GENERASI MILLENIAL DI UNIVERSITAS MUHAMMADIYAH MALANG - Nanang Khosim; I’anatut Thoifah (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2020)
There are many graduates of Islamic religious universities who have not been able to read Qur’an, even, it is stated in the statistical data center that 54 percent of all Muslims in Indonesia cannot read Qur’an. Therefore, this study investigates the patterns of Qur’an Learning and the obstacle factors during the implementation of the program.In obtaining the data, this descriptive qualitative research uses observation, interviews, and documentation which are analyzed as the results of the study.The results of this study indicated that the learning patterns implemented in Al Qur’an Literacy Program at Muhammadiyah University of Malang are the patterns of teacher and media. In other words, the teachers make use of various learning media as the learning sources. Although not all patterns are not fully applied by the teachers, the patterns which have been carried out by the teachers were quite well by arranging better plans during the implementation of the program. Meanwhile, the obstacle factors of this program are the students are not able to learn individually due to the lack of meetings which requires personal awareness of students who learn Qur’an to increase literacy through inquiry learning. Besides, no institution can back up the program after the completion of Al Qur’an Literacy Program as the balancing and evaluation of achieving the target of graduates in the program of Al Qur’an Literacy.